Une histoire asynchrone de l’économie et de l’écologie, et de leurs « passeurs » - Sophie Boutillier; Patrick Matagne (VertigO)
Economics becomes a science at the end of the 18th century with the Classical and Physiocratic schools. These both schools of thinking consider the market as the ideal form of the economic activity and they did not analyze the problem of depletion of natural resources. Work and trade are at the heart of the wealth of nations. Nevertheless, pollution was not an unknown fact of European populations, as historians’ works demonstrate. Ecology becomes a science one hundred years later, showing the difficult balance between human activities and natural resources. The aim of this study is to show that despite this gap of 100 years, economists have studied environmental problems, and on the other hand, scientists, especially biologists, have studied the impact of human activities on the environment. We call them “boatmen”.